*Hemodynamic effect of somatostatin infusion in patients with non-variceal upper gastrointestinal bleeding - Murat SARUÇ; Mine CAN; Nurten KÜÇÜKMETİN; Cihan GÖKTAN; Hakan YÜCEYAR (Turkish Journal of Gastroenterology, 2019)
-